Viral respiratory infections in hospitalized and community control children in Alaska†, ‡ - Singleton, Rosalyn J.; Bulkow, Lisa R.; Miernyk, Karen; DeByle, Carolynn; Pruitt, Lori; Hummel, Kimberlee Boyd; Bruden, Dana; Englund, Janet A.; Anderson, Larry J.; Lucher, Lynne; Holman, Robert C.; Hennessy, Thomas W.
Respiratory syncytial virus (RSV) in Alaska Native children from the Yukon Kuskokwim (YK) Delta is associated with a hospitalization rate five times higher than that reported for the general US child population. The role of other viral respiratory pathogens has not been studied in this population. YK Delta children <3 years of age hospitalized with respiratory infections and same aged community control children were prospectively enrolled between October 2005 and September 2007. Polymerase chain reaction detection of viruses was performed on nasopharyngeal samples. Characteristics of hospitalized and asymptomatic control children were analyzed. From October 2005 to September 2007, 440 hospitalized and 425 control children were analyzed. Respiratory viruses were detected in 90% (395) of hospitalized children: 194 (44%) rhinovirus, 131 (30%) adenovirus, 102 (23%) RSV, 77 (18%) para influenza viruses (PIV), 66 (15%) human metapneumovirus (hMPV), 23 (5%) influenza, and 25 (6%) coronavirus. Fifty-two percent (221) of control children had a virus detected, most commonly rhinovirus (33%), and adenovirus (16%). RSV, PIV, hMPV, and influenza were significantly more common in hospitalized cases than control children, but rhinovirus, adenovirus, and coronavirus were not. RSV and hMPV were associated with higher severity of illness. In this study, RSV remains the most important virus associated with respiratory hospitalization, although hMPV and PIV were also common. RSV and hMPV were associated with more severe illness. Rhinovirus and adenovirus were detected in two-thirds of hospitalized children, but their frequent detection in control children made their role in respiratory hospitalization uncertain.